P163 Biosamples from at risk SSc patients show classic pathological signs of scleroderma: opportunity for a diagnosis of pre-clinical SSc. (20th April 2020) - Ross, Rebecca L; Georgiou, Ioanna; Carriero, Antonio; Abignano, Giuseppina; Wasson, Chris; Migneco, Gemma; Herrick, Ariane; Denton, Chris; Galdo, Francesco Del
Abstract: Background: The VEDOSS study has recently indicated that more than 80% of patients affected by Raynaud's phenomenon (RP) and specific SSc auto-antibodies + capillaroscopy changes satisfied ACR/EULAR 2013 criteria within 5 years.These data suggest that there is a window of opportunity for early detection of SSc in these patients. Here we aimed to determine whether sera, skin biopsies and skin fibroblasts cultured from these patients showed any biomarker sign of SSc. Methods: Fifty-nine at risk patients identified by having RP and SSc auto-antibodies or capillaroscopy pattern (or both) were enrolled in the national inception cohort (Kennedy Cohort). Sera were tested for IFN inducible chemokines (CXCL-9, 10 and 11 and CCL2, 8 and 19) and biomarker of extracellular matrix turnover (ELF test), all previously shown to be increased in SSc. Further, two 3mm skin biopsies were taken from the forearms from 3 ACA+ve (anti-centromere antibodies), 3 SCL70+ve patients. One biopsy was subjected to histology analysis, including haematoxylin and eosin staining and immunohistological staining for Collagen Type 1, alpha-SMA, Caveolin 1 and CD31 as endothelial marker. The other biopsy was used to explant fibroblasts cultures. mRNA and protein were isolated from primary fibroblasts and processed for RT-qPCR and western blotting analyses. Results: Sera from at risk patients showed overall higher IFN inducible chemokines and ELF test (P < 0.05) with bimodal distribution among patients. Skin biopsies from both ACA or SCL70+ve patients showed decreased number of CD31+ cells, increased number of myofibroblasts and increased collagen bundles within the dermis, as usually seen in SSc, compared to healthy controls. In vitro, fibroblasts from both ACA or SCL70+ve patients showed average 10-fold higher collagen mRNA levels and 31-fold increased collagen protein levels compared to healthy control fibroblasts. Furthermore, fibroblasts from ACA or SCL70+ve patients showed limited TGF-beta induced increase in collagen and SMA expression, similar to SSc fibroblasts. Conclusion: Although pilot in nature, this study suggests that patients "at risk" already show biomarker signs of SSc both in their sera and at skin biopsy and fibroblast level. Longitudinal studies on patients at this stage of pre-clinical disease may inform on the stratification strategies for imminent progression to clinical manifestations and offer both insights on pathogenesis of clinical signs and a window of opportunity for delaying the onset clinical intervention trials. Disclosures: R.L. Ross None. I. Georgiou None. A. Carriero None. G. Abignano None. C. Wasson None. G. Migneco None. A. Herrick None. C. Denton None. F. Del Galdo None.